Diabetic ketoacidosis in patients with type 2 diabetes treated with sodium glucose co‐transporter 2 inhibitors versus other antihyperglycemic agents: An observational study of four US administrative claims databases. Issue 12 (27th August 2019) - Wang, Lu; Voss, Erica A.; Weaver, James; Hester, Laura; Yuan, Zhong; DeFalco, Frank; Schuemie, Martijn J.; Ryan, Patrick B.; Sun, Don; Freedman, Amy; Alba, Maria; Lind, Joan; et al.
Abstract: Purpose: To compare the incidence of diabetic ketoacidosis (DKA) among patients with type 2 diabetes mellitus (T2DM) who were new users of sodium glucose co‐transporter 2 inhibitors (SGLT2i) versus other classes of antihyperglycemic agents (AHAs). Methods: Patients were identified from four large US claims databases using broad (all T2DM patients) and narrow (intended to exclude patients with type 1 diabetes or secondary diabetes misclassified as T2DM) definitions of T2DM. New users of SGLT2i and seven groups of comparator AHAs were matched (1:1) on exposure propensity scores to adjust for imbalances in baseline covariates. Cox proportional hazards regression models, conditioned on propensity score‐matched pairs, were used to estimate hazard ratios (HRs) of DKA for new users of SGLT2i versus other AHAs. When I 2 <40%, a combined HR across the four databases was estimated. Results: Using the broad definition of T2DM, new users of SGLT2i had an increased risk of DKA versus sulfonylureas (HR [95% CI]: 1.53 [1.31‐1.79]), DPP‐4i (1.28 [1.11‐1.47]), GLP‐1 receptor agonists (1.34 [1.12‐1.60]), metformin (1.31 [1.11‐1.54]), and insulinotropic AHAs (1.38 [1.15‐1.66]). Using the narrow definition of T2DM, new users of SGLT2i had an increased risk of DKA versus sulfonylureas (1.43 [1.01‐2.01]). New users of SGLT2i had a lower risk of DKA versus insulin and a similar risk as thiazolidinediones, regardless of T2DM definition. Conclusions: Increased risk of DKA was observed for new users of SGLT2i versus several non‐SGLT2i AHAs when T2DM was defined broadly. When T2DM was defined narrowly to exclude possible misclassified patients, an increased risk of DKA with SGLT2i was observed compared with sulfonylureas.